THE IMPACT OF COVID-19 PANDEMIC ON SERVICES FOR PERSONS WITH NEURODEVELOPMENTAL DISORDERS: AN ITALIAN CASE - Zorzi, Simone (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The COVID-19 pandemic has had severe effects on social health services worldwide. Many people with neurodevelopmental disorders have lost their professional support. The interruption of supportive assistance has been devastating since it has negatively affected their continuity of care as well as their social inclusion and socialization. This paper aims to illustrate the impact of the COVID-19 on an Italian Public Social Health System Services for people with disability. It highlights and discusses the strategy that was adopted in order to ensure the continuity of care assistance provided to the service clients as the organization of emergency remote support and individual support services for independent living. An exploratory study was conducted involving the entire population of people with neurodevelopmental disorders (n=333) included in the Disability System Services of Udine (Friuli Venezia Giulia Region, North-East Italy) to analyze the main repercussions occurred on the organization of services during the pandemic period. A comparative analysis of the number of persons enrolled in the different types of support services and of individuals’ support needs, evaluated throught the Support intensity scale (SIS), pre- and post-pandemic crisis (January 2020 – January 2021) was conducted. The data shows that, despite the enormous difficulties, the adopted strategy has succeeded in limiting the risks of isolation and the negative impact on individual interventions, and opened the way to new alternative and innovative strategies for planning and implementing support.